2015
DOI: 10.4018/ijmtie.2015010102
|View full text |Cite
|
Sign up to set email alerts
|

Detection of UV Rays Using CdTe Quantum Dots

Abstract: Development of simple UV detection system using CdTe quantum dots (QDs) as primary detector with scintillating property on exposure to UV rays is reported. CdTe, CdTe/ZnS and CdTe/CdS QDs were synthesized in aqueous phase using mercaptosuccinic acid (MSA) as a capping agent and studied for its properties like crystallite size, band gap energy, fluorescence emission intensity and uniformity in size distribution. The prepared QDs were exposed to different radiations such as infrared (IR), ultraviolet (UV) and X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Several research works have already been reported on the response of metallic QDs to UV irradiation [32,33,[52][53][54]. Conversely, no illumination was observed when QDs were exposed to low-energy infrared radiation, and exposure of QDs to high-energy radiation such as X-rays leads to QD damage [52]. Some previous studies revealed that QD exposure to UV radiation releases heavy metal ions from these nanomaterials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several research works have already been reported on the response of metallic QDs to UV irradiation [32,33,[52][53][54]. Conversely, no illumination was observed when QDs were exposed to low-energy infrared radiation, and exposure of QDs to high-energy radiation such as X-rays leads to QD damage [52]. Some previous studies revealed that QD exposure to UV radiation releases heavy metal ions from these nanomaterials.…”
Section: Discussionmentioning
confidence: 99%
“…Derfus et al [33] reported the release of free Cd 2+ ions from cadmium selenide (CdSe) QDs in the presence of UV radiation as a consequence of QDs surface oxidation. It was found that CdTe QDs also respond to UV radiation [6,32,52,53]. UV exposure causes the release of Cd 2+ ions from the CdTe QD surface.…”
Section: Discussionmentioning
confidence: 99%